CFD Analysis of Falling Film Hydrodynamics for a Lithium Bromide (LiBr) Solution over a Horizontal Tube - Furqan Tahir (14429547) (2020)
Falling film evaporators are used in applications where high heat transfer coefficients are required for low liquid load and temperature difference. One such application is the lithium bromide (LiBr)-based absorber and generator. The concentration of the aqueous LiBr solution changes within the absorber and generator because of evaporation and vapor absorption. This causes the thermophysical properties to differ and affects the film distribution, heat, and mass transfer mechanisms. For thermal performance improvement of LiBr-based falling film evaporators, in-depth analysis at the micro level is required for film distribution and hydrodynamics. In this work, a 2D numerical model was constructed using the commercial CFD software Ansys Fluent v18.0. The influence of the liquid load corresponding to droplet and jet mode, and the concentration, on film hydrodynamics was examined. It was found that the jet mode was more stable at a higher concentration of 0.65 with ±0.5% variation compared to lower concentrations. The recirculation was stronger at a low concentration of 0.45 and existed until the angular position (θ) = 10°, whereas at 0.65 concentration it diminished after θ = 5°. The improved heat transfer is expected at lower concentrations due to lower film thickness and thermal resistance, more recirculation, and a higher velocity field. Other Information Published in: Energies License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/en13020307